Retroprosthetic Membrane Formation in Boston Keratoprosthesis Type 1: Incidence, Predisposing Factors, Complications, and Treatment. Issue 6 (5th June 2022) - Khair, Diana; Daoud, Roy; Harissi-Dagher, Mona
Abstract : Purpose: The purpose of this study was to evaluate the incidence, rate of formation, and risk factors of retroprosthetic membrane (RPM) after Boston type 1 keratoprosthesis (BKPro) as well as identify secondary complications linked to its formation and describe its treatment. Methods: This was a retrospective cohort study. One hundred thirty-three eyes of 115 patients who underwent BKPro implantation at the Centre Hospitalier de l'Université de Montréal from 2008 to 2017 were included with at least 1-year follow-up. Charts were reviewed, and data were collected, including incidence of RPM formation, preoperative and intraoperative risk factors, postoperative complications, and treatment modalities. Results: The mean follow-up was 5.5 years, and 39% (n = 52) of eyes developed RPM. No etiologies were found to be significantly associated with RPM development. Simultaneous lensectomy and simultaneous intraocular lens extraction were respectively positively and negatively correlated with RPM development [odds ratio (OR): 0.3590, 95% CI: 0.1629–0.7570, P = 0.0097; OR = 2.646, 95% CI: 1.273–5.585, P = 0.0086, respectively]. As for postoperative complications, the strongest correlation was between RPM and retinal detachment (OR = 6.16, 95% CI: 2.14–16.14; P = 0.0004). RPM development was also positively associated with the development of hypotony and corneal melt. Nd:YAG membranectomy was the most common treatment, performed in 83% of eyes with RPM (n = 24), with 58% resolution. Conclusions: More than one third of patients who undergo BKPro will develop RPM, requiring close monitoring for retinal detachment. Simultaneous intraocular lens extraction seems protective, whereas simultaneous lens extraction increases the rate of RPM formation significantly. Nd:YAG membranectomy can be used as an initial noninvasive approach.